THERAPY-RELATED MYELOID NEOPLASMS: CONSIDERATIONS FOR PATIENTS’ CLINICAL EVALUATION. - Raffaele Palmieri; Ilaria Del Principe; Luca Maurillo; Adriano Venditti; Francesco Buccisano (Mediterranean Journal of Hematology and Infectious Diseases)
Therapy-related myeloid neoplasms (t-MNs) encompass a specific sub-group of myeloid malignancies arising after exposure to radio/cytotoxic agents for the treatment of unrelated diseases.